Descending with angels : islamic exorcism and psychiatry : a film monograph - Suhr, Christian, 1978- (Anthropology, creative practice and ethnography., 2019)
Over several years, Christian Suhr followed Muslim patients being treated for jinn possession and psychosis in a Danish mosque and in a psychiatric hospital. Through rich filmic and textual case studies, he shows how the bodies and souls of Muslim patients become a battlefield between the moral demands of Islam and the psychiatric institutions of European nation-states. The book reveals how both psychiatric and Islamic healing work to produce relief from pain, and also entail an ethical transformation of the patient and the cultivation of religious and secular values through the experience of pain. Creatively exploring the analytic possibilities provided by the use of a camera, both text and film show how disruptive ritual techniques are used in healing to destabilise individual perceptions and experiences of agency, which allows patients to submit to the invisible powers of psychotropic medicine or God.